Isoscaling of mass A ≃ 40 reconstructed quasiprojectiles from collisions in the Fermi energy regime - Galanopoulos, S.; al., et (HNPS Advances in Nuclear Physics, 2019)
Isoscaling studies of fragments with Z=1-8 from reconstructed quasiprojectiles of mass A ≃40 from the 40Ca + 112,124Sn and 40Ar + 112,124Sn reactions at beam energy of 45 MeV/nucleon were performed. After initial efforts to obtain isoscaling using pairs of systems differing in their neutron-to-proton ratio N/Z, “intra-system” isoscaling for each of these four systems was obtained using fragment sources restricted in two narrow N/Z zones, one neutron rich and one neutron poor. The observed isoscaling behaviour was excellent and the isoscaling parameter α was found to decrease as the excitation energy increases. Corrections due to undetected neutrons were also taken into account in the source N/Z determination by using the theoretical models DIT (Deep Inelastic Transfer) and SMM (Statistical Multifragmentation Model) along with a software replica of the experimental setup. The reduced isoscaling parameter α/∆ was found to decrease as the excitation energy of the quasiprojectile source increases, in good agreement with recent work on reconstructed mass A ≃ 80 quasiprojectiles. This decrease of α/∆ may point to a decrease of the symmetry energy coefficient with increasing excitation energy.